Inhibition by sodium nitroprusside of a calcium store depletion-activated non-selective cation current in smooth muscle cells of the mouse anococcygeus. - Wayman, C. P. (1996)
1. The effects of sodium nitroprusside (SNP) on the non-selective cation current activated in response to intracellular calcium store depletion were studied using the whole-cell patch-clamp technique in single smooth muscle cells isolated from the mouse anococcygeus. Voltage-dependent calcium currents were blocked with extracellular nifedipine, and caesium and tetraethylammonium chloride were used to block voltage-dependent potassium currents. Calcium stores were depleted with caffeine (10 mM), carbachol (50 microM) or cyclopiazonic acid (CPA 10 microM; an inhibitor of the sarcoplasmic reticulum [SR] calcium-ATPase). 2. At a holding potential of -40 mV, both CPA and caffeine activated inward currents which consisted of two clearly distinguishable components; an initial transient current followed by a smaller sustained current. In the case of CPA, the amplitudes of the transient and sustained components were 19.7 +/- 2.1 pA and 3.5 +/- 0.3 pA respectively, whilst the equivalent values for caffeine were 188 +/- 21 and 4.8 +/- 0.3 pA. As described previously, the transient current results from activation of a calcium-dependent chloride conductance whilst the sustained current is a non-selective cation current, activated following intracellular calcium store depletion. 3. The muscarinic receptor agonist, carbachol, also activated a transient followed by a sustained current with amplitudes of 238 +/- 55 and 4.7 +/- 0.5 pA respectively. Superimposed on the sustained current were regular, oscillations of calcium-activated chloride current. 4. Both the transient and the sustained currents activated by CPA were absent in cells pretreated with SNP (10 microM). Application of SNP to a cell following activation of the sustained current by CPA inhibited the current by 88.6 +/- 3.8%. SNP (10 microM) did not inhibit the transient current activated by caffeine but abolished the sustained current. 5. SNP (10 microM) had no effect on the initial transient current activated by carbachol (50 microM). However, it did inhibit the oscillations in the inward current. In recordings from cells bathed in extracellular solution containing the chloride channel blocker, anthracene-9-carboxylic acid (A-9-C; 1 mM), carbachol activated only a sustained current. This current was inhibited by 88.1 +/- 6.5% by a concomitant application of SNP (10 microM) and was absent in cells pretreated with the nitrovasodilator. 6. The effects of SNP on the currents activated by caffeine (10 mM) were mimicked by 8-bromo-cyclic GMP (200 microM); thus the nucleotide had no effect on the transient current activated by caffeine but abolished the sustained current. The effects of SNP, but not those of 8-bromo-cyclic GMP, were inhibited by the nitric oxide-sensitive guanylyl cyclase inhibitor, 1H-[1, 2, 4]oxadiazolo[4, 3-a]quinoxaline-1-one (ODQ; 1 microM). ODQ alone produced a significant increase in the size of the sustained current activated by caffeine (7.8 +/- 0.7 pA). 7. These findings suggest that SNP activates guanylyl cyclase to inhibit the non-selective cation current activated as a result of intracellular calcium store depletion in mouse anococcygeus cells. Since the non-selective cation current appears to underlie the calcium entry process responsible for maintaining the sustained contractions to agonists in this tissue, this action of SNP may represent an important mechanism by which nitrates relax non-vascular smooth muscle.